Female Educational Empowerment and Fertility Behaviour - Samina Badar , Seemi Gull , Muhammad Akram Saeed, Wajahat Hussain (Journal of Rawalpindi Medical College, 2013)
Background: To find out the relationship between educational level and fertility behavior. Methods: In this cross sectional study Bahawalpur (municipality area) was stratified on the judgmental basis into relatively upper, middle and lower class localities. On the basis of contraceptive prevalence rate (CPR) 23.20%7 the minimum sample size of 733 was calculated with 3% precision and at 95% confidence interval. A list of all households with married women of reproductive age (15-49 years) having at least one child of more than 2 years of age was obtained from LHWs of the area. Out of 4884 households 733 eligible women were included in the study by simple random sampling procedure by taking proportionate sample of all classes (133 out of 884, 173 out of 1154 and 427 out of 2846). Data was collected by using pretested structured questionnaire with the help of lady health workers of that area with their supervisors. Collected data was entered and analyzed by using SPSS 17. Results: In a total of 733 married women in the study, 53.4% (392) women were literate. Among the literate women 81% were matriculate and above. Among literate women 74.7% were user of contraceptive methods compared with 51.3% illiterate women. Number of children of respondents with level of education showed that significant relationship (p<0.001) was found. It was observed that 51.2% of low, 71.1% of medium and 75.6% of high educational level women were using contraceptives. Conclusion: Level of education has direct relationship with use of contraceptive and inverse relationship with number of children.